STRATEGIC MANAGEMENT OF GREEN TRANSFORMATION PROCESSES IN TERRITORIAL COMMUNITIES - Klochan, Viacheslav; Andreichenko, Andrii; Podmazko, Oleksii (Current Problems of Sustainable Development, 2026)
The article is devoted to the study of strategic management of green transformation processes in territorial communities as an urgent area of local public policy under the conditions of decentralization, European integration requirements, and the need for post-war recovery. The scientific problem addressed in the article does not lie in the lack of declared green priorities, but in the absence of their systematic integration into the full management cycle, including strategic planning, operational plans, budget programmes, project portfolios, partnerships, and monitoring. The methodological basis of the study is formed by a set of research methods, including the systems approach, structural and logical analysis, strategic analysis, elements of SWOT analysis, the expert- analytical approach, and the case study method. Based on the analysis of six managerial dimensions of green transformation – economic, infrastructural, energy-related, spatial planning, social, and institutional – the key managerial barriers are identified. These include the fragmentation of strategic documents, limited project capacity, weak intersectoral coordination, and insufficient public participation. The article proposes an original model of strategic management of green transformation, which covers seven consecutive stages: from diagnosing the current state of a community to policy adjustment. Practical testing of the proposed approach was carried out on the case of Savran settlement territorial community in Odesa Oblast. For this community, the priority areas of green transformation and the tools for their strategic integration were identified. The results of the study are of practical importance for local self-government bodies, regional development agencies, and organizations that support strategic planning processes in territorial communities.
Keywords: strategic management; green transformation; territorial communities; sustainable local development; institutional capacity; portfolio of green projects